A plasmonic liquid junction photovoltaic cell with greatly improved power conversion efficiency. Issue 92 (26th October 2016) - Lee, Woo-ram; Navarrete, Jose; Evanko, Brian; Stucky, Galen D.; Mubeen, Syed; Moskovits, Martin
Abstract : A novel and improved plasmon liquid-junction PV cell is reported by engineering the optical absorption of the plasmonic electrode and interfacial energetics of the contacting electrolyte. Abstract : A plasmonic liquid junction photovoltaic cell with greatly improved power conversion efficiency is described. When illuminated with simulated sunlight, the device (Au–TiO2 /V 3+ (0.018 M), V 2+ (0.182 M)/Pt) reproducibly and sustainably produces an V OC of 0.50 V and a J SC of 0.5 mA cm −2, corresponding to a power conversion efficiency of 0.095%.